CITRA SPIRITUALITAS MASYARAKAT JAWA DALAM SEJARAH SENI PERTUNJUKAN WAYANG - Joko Sujarwo; Radhitya Kusuma Negara; Rizky Kusuma Adi; Gibson Samuel Imbenai; Tegar Taryan Margatama; Albertus Prasojo; Yunior Dhian Bagaskara (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
The art of wayang performance is one of the traditional cultures of the Javanese people. As part of culture, wayang records the spirituality of the Javanese people as the artist. This study aims to determine the image of Javanese spirituality in wayang performances. This paper includes a qualitative-descriptive study. The data in this study are in the form of narratives about the spirituality of the Javanese people and history of wayang performing arts. The data for this study were collected using literature study, reading and note-taking techniques. The analysis model used in this paper is descriptive. Data that has been collected, reduced, then presented. The results of the study show that the history of wayang performing arts can be divided into three periods, namely the animism-dynamism, Hindu-Buddhism, and Islam. The charting period shows the development of the spirituality of the Javanese people. The history of wayang as a performing art seems to accompany the changes in the spirituality of the Javanese people, starting from totemism, polytheism, to monotheism.